Configuring Retail Fulfillment Processes for Omni-Channel Customer Steering. Issue 4 (2nd October 2018) - Wollenburg, Johannes; Holzapfel, Andreas; Hübner, Alexander; Kuhn, Heinrich
ABSTRACT: The fulfillment of customer orders has gained a particularly important role within omni-channel retailing, as it requires significant effort to integrate logistics networks and product flows. Offering additional fulfillment options is costly but allows the enhancement of customer services via cross-channel substitutions and faster deliveries. Retailers are asking themselves how they can leverage these integrated systems to improve return on investment as well as customer service. One option is to influence customers' channel choice (i.e., steering). Because this has so far mainly been viewed from a marketing perspective, this study investigates how and why different fulfillment options can help to steer customers across channels. By using multiple sources of data (i.e., market data, retailer interviews, customer focus groups), this paper identifies how customers can be guided through channels by means of related options in inventory management (e.g., cross-channel inventory information and substitution), delivery modes (e.g., differentiation of prices and delivery velocity across channels), and return modes (e.g., pricing for returns and options to return goods in-store). In essence, this research paper contributes a theory of cross-channel customer steering by means of different fulfillment options.